2018
DOI: 10.1080/14756366.2018.1443326
|View full text |Cite
|
Sign up to set email alerts
|

Profiling donepezil template into multipotent hybrids with antioxidant properties

Abstract: Alzheimer’s disease is debilitating neurodegenerative disorder in the elderly. Current therapy relies on administration of acetylcholinesterase inhibitors (AChEIs) -donepezil, rivastigmine, galantamine, and N-methyl-d-aspartate receptor antagonist memantine. However, their therapeutic effect is only short-term and stabilizes cognitive functions for up to 2 years. Given this drawback together with other pathological hallmarks of the disease taken into consideration, novel approaches have recently emerged to bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 167 publications
2
33
0
Order By: Relevance
“…One of the derivatives of 79 , for which X = H, R 1 = CF 2 H, R 2 = cyclopentylethyl, exhibited an IC 50 of 0.399 mM against PDE4D compared to rolipram as the reference compound (IC 50 0.621 mM), whereas the derivative showing X = H, R 1 = cyclopentylmethyl of family 84 exhibited the highest value among all tested compounds in the ORAC assay (its value is 1.98 expressed as Trolox equivalents). In this respect, the ORAC value of antioxidant activities increases the ability of a given compound as the antioxidant becomes better [ 58 ]. Clioquinol, rolipram, and roflumilast showed values of 0.60, 0.070, and 0.067, respectively.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…One of the derivatives of 79 , for which X = H, R 1 = CF 2 H, R 2 = cyclopentylethyl, exhibited an IC 50 of 0.399 mM against PDE4D compared to rolipram as the reference compound (IC 50 0.621 mM), whereas the derivative showing X = H, R 1 = cyclopentylmethyl of family 84 exhibited the highest value among all tested compounds in the ORAC assay (its value is 1.98 expressed as Trolox equivalents). In this respect, the ORAC value of antioxidant activities increases the ability of a given compound as the antioxidant becomes better [ 58 ]. Clioquinol, rolipram, and roflumilast showed values of 0.60, 0.070, and 0.067, respectively.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Similarly, the use of galantamie, donepezil, and rivastigmine in mild to moderate AD provide modest cognitive function and behavior as reviewed by Mohammad 67 . Furthermore, profiling donepezil template into multipotent hybrids through molecular docking has shown that it has anticholinesterase activity with escalating antioxidant potential 68 .…”
Section: Nootropicsmentioning
confidence: 99%
“…However, none of the new drug candidates have a real impact on the outcome of the disease . The multifactorial origin of AD encouraged new approaches for drug design, as multitarget design programs . The development of multitarget hybrid agents based on well‐known bioactive compounds is becoming a widely used strategy.…”
Section: Introductionmentioning
confidence: 99%